Maturity level of female red swimming crab gonads (Thalamita spinimana) in Dompak Waters, Tanjungpinang, Riau Island - Sri Novitri; Susiana; Wahyu Muzammil; Dedy Kurniawan (Akuatikisle: Jurnal Akuakultur, Pesisir dan Pulau-Pulau Kecil, 2021)
Red crab (Thalamita spinimana) is a type of crab that has a light body color, favored by coastal communities for its thick meat and high protein content at a low selling price. This research purpose to determine the maturity level of female red crabs. This research was conducted using a survey method with sampling twice for two months which was carried out from April to May 2021 in Dompak Waters, Tanjungpinang. The results of the research found that TKG I was immature gonads. Female red crabs incubate eggs (Ovigerous) with yellow and orange color, dominated by immature gonads, while brown and dark gray colors are dominated by mature gonads.